Sistem Cerdas Penentuan Biji Kopi Robusta Terbaik Berbasis AHP Pada Industri Rumah Tangga JS Family Simpang Kanan Sumberejo Tanggamus, Lampung - Dwi Handoko; Ahmad Syarifuddin; Elystia Febriyanti (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
JS Family Home Industry is a home industry engaged in the production of Robusta coffee, namely from intact coffee beans and then processing them into ground coffee which is packaged in sachets to be sold and enjoyed by coffee connoisseurs. Because of that, an intelligent system is needed to help in these business activities, namely a smart system to determine the best Robusta coffee beans. Determination of robusta coffee beans in the JS Family Home Industry is still carried out manually, namely in the traditional way that relies on an empirical knowledge base and is still not professional so that the quality of the coffee that will be processed into IKI Coffee products cannot be known with certainty whether the quality of the coffee is good or not so good.Seeing the problems that exist, researchers try to create and design an intelligent system with a good computerized system design that aims to help IKI Coffee products from the JS Family Home Industry. This system uses the Java programming language and SQL Server 2000 database. This system also use AHP methode because in determining the best robusta coffee beans, several criteria are needed and try whether the AHP method can be used to determine the best robusta coffee beans or not.Based on the results of the research conducted, the conclusions that can be drawn are to simplify the process of determining the best Robusta coffee beans and find out how good the quality of the good Robusta coffee beans.